Sampling and choosing cases in qualitative research - Emmel, Nick. (London : SAGE, 2013)
Helping students to become familiar with various sampling techniques and how to make empirical and theoretical claims from the cases they choose, this text introduces widely used sampling methodologies and identifies key theoretical assumptions.
Keywords: Social sciences; Qualitative research; Qualitative research; Social sciences; Samhällsvetenskaplig forskning; Kvalitativ metod; Society